Conservative Laparoscopic Approach for the Management of a 14-Week Viable Ectopic Cesarean Scar Ectopic Pregnancy - Wael Elbanna; Osama Azmy (Hindawi Limited, 2024)
Conclusion: This case highlights the importance of a conservative laparoscopic approach for CSEP in the second trimester. Imaging techniques play a pivotal role in accurate diagnosis, with minimally invasive technologies offering effective solutions. Individualized, patient-centered approaches are necessary to prioritize clinical outcomes and patient preferences.